COMMUNICATION APPROACH ON TAX ENFORCEMENT IN BUILDING TAX COMPLIANCE IN INDONESIA - Musaiyana (Scientia Integritas Utama, 2024)
Tax enforcement should be able to influence the public's view of tax compliance, through communication approach which is a form of influencing the view of society from non-penal to overcome tax evasion. This inability can be seen from several empirical facts, such as the low audit coverage ratio and still having to face challenges in the form of high levels of tax objection submissions. Based on conseptual approach, this articlr produces two conclusions. First, tax enforcement in Indonesia is currently taking inventory of the flow of legal information between senders and recipients, not yet reaching an open tax system in order to influence tax compliance. Second, effective legal communication in tax enforcement in Indonesia can be carried out through building legal morality, because it is able to create a tax (legal) system that is open and can be understood and accepted by the parties communicating in tax enforcement. It is recommended that there be regular training and webinars on legal communication with tax enforcers in Indonesia.